Strategies for genome-wide association analysis: gene-centric approach, network-based analysis and copy number variants: 1st Triennium Post Doc Fellowship report - Tavares Correia, Catarina Alexandra (2014)
Fellowship: SFRH/BPD/ 64281/2009